Happiness in the early childhood education workforce: An explanatory sequential mixed methods study - Julia Pangalangan; Emily Mauirro; Charlotte Farewell; Jini Puma (Journal of Happiness and Health)
The early childcare and education (ECE) workforce shapes the developmental outcomes of children during critical years of growth. Despite facing historically low wages and high demands, the ECE workforce is happier than the general population in the U.S., with happiness levels comparable to Iceland and other top-ranking countries. PERMA, a model that identifies five elements that contribute to flourishing (positive emotions, engagement, relationships, meaning, and accomplishment), can been used to promote wellbeing. This explanatory sequential mixed methods study aimed to investigate the work-related PERMA components that predict happiness levels in the early childhood (ECE) workforce. A hierarchical linear regression revealed that the PERMA components did significantly predict happiness in this sample of ECE staff, R2 = 0.20, F(10,244) = 5.96, p <.001. Engagement, positive emotions, and meaning at work were found to significantly account for the variance in happiness, after controlling for the other variables in the model. Qualitative interviews provided further insight into perceptions of happiness among ECE staff, supporting the value of relationships and meaning in ECE settings. This is the first mixed methods study to assess predictors and perceptions of happiness in the ECE workforce and has important research and practice implications for supporting mental health in this critical population.